Role of the microtubules in the electrical activity of the primary cilium of renal epithelial cells - Scarinci, Noelia; Gutierrez, Brenda C.; Albarracín, Virginia H.; Cantero, María del Rocío; Cantiello, Horacio F. (Frontiers in Molecular Biosciences, 2023)
The primary cilium is a non-motile sensory organelle that transduces environmental cues into cellular responses. It comprises an axoneme, a core of nine doublet microtubules (MTs) coated by a specialized membrane populated by receptors, and a high density of ion channels. Dysfunctional primary cilia generate the pathogenesis of several diseases known as ciliopathies. However, the electrical role of MTs in ciliary signaling remains largely unknown. Herein, we determined by the patch clamp technique the electrical activity of cytoplasmic and axonemal MTs from wild-type LLC-PK1 renal epithelial cells. We observed electrical oscillations with fundamental frequencies at ~39 Hz and ~93 Hz in sheets of cytoplasmic MTs. We also studied in situ and isolated, intact and Triton X-permeabilized primary cilia, observing electrical oscillations with peak frequencies at either 29-49 (non-permeabilized) or ~40-49 Hz (permeabilized) and ~93 Hz (both). We applied Empirical Mode Decomposition (EMD), Continuous Wavelet Transform (CWT), and Cross-Correlation Analysis (CCA) to assess the differences and the coherence in the Time-Frequency domains of electrical oscillations between cytoplasmic and axonemal MTs. The data indicate that axonemal and cytoplasmic MTs show different patterns of electrical oscillations preserving coherence at specific frequency peaks that may serve as electromagnetic communication between compartments. Further, the electrical behavior of axonemal MTs was modified by siRNA deletion of polycystin-2 (PC2), which lengthens primary cilia, thus linking ciliary channels to the morphological and electrical behavior of cilia in ciliopathies. The encompassed evidence indicates that the primary cilium behaves as an electrical antenna, with an excitable MT structure that produces electrical oscillations whose synchronization and propagation constitute a novel cell signaling mechanism.